Buccal mucosal hypertrophy secondary to open bite - S Nilima; Anuj Sharma (Wolters Kluwer Medknow Publications, 2015)
Timely and accurate diagnosis of a medical/dental condition is the first critical step to ensure appropriate treatment. Lack of astuteness in diagnosis may assume many forms. Each medical/dental practitioner is morally and legally bound to perform his or her duties to a specified standard of care. The cause of misdiagnosis may be hurriedness, lack of testing, or a simple mistake; failure to diagnose can constitute a breach of that duty, making the medical/dental provider liable for any resulting damages. The following case report highlights one such misdiagnosed case.